Percursos e desafios na atuação dos conselhos de acompanhamento e controle social do município de Cachoeira do Sul/RS - Puntel, Michele (2022)
This study is part of the Programa de Pós-graduação em Políticas Públicas e Gestão Educacional (PPPG), at the Universidade Federal de Santa Maria - RS (UFSM), developed in Linha de Pesquisa I: Políticas Públicas e Gestão da Educação Básica e Superior, linked to the set of works and productions of the research project (umbrella) of the Study and Research in Policies and Educational Management REDES/UFSM group, which carries out research and studies on public policies and educational management considering the dialogue between Basic Education and Higher, which has as its theme the investigation of the paths and challenges in the performance of the Conselhos de Acompanhamento e Controle Social (CACS) of the Fundo de Manutenção e Desenvolvimento da Educação Básica e de Valorização dos Profissionais da Educação (Fundeb) and the Programa de Alimentação Escolar in the municipality of Cachoeira do Sul/RS. The research proposal is justified by the importance of establishing a dialogical analysis with the course of action of the Conselhos de Acompanhamento e Controle Social (CACS), which are expressed through a democratic space, which encourages the shared management of different social segments in the supervision and social control of resources for the financing of public education. The research problem is: how are public education resources used and how is this action linked to the monitoring performed by society through the CACS, and how is this construction and/or consolidation of public policies for education management being perceived? To meet this intention, it was defined as a general objective to analyze the paths and challenges in the performance of CACS Fundeb and Alimentação Escolar in the daily life of educational management in relation to social control and the application of resources for the financing of education in Cachoeira do Sul/RS; and as specific objectives: To investigate the perception and action of the Conselhos de Acompanhamento e Controle Social (CACS) linked to the legislation that instituted them; to verify the system of monitoring and follow-up of the councils with respect to the effectiveness of the role in social control; to identify the revenues destined to municipal public education and destination of the expenses that are pertinent to the educational public policies; to elaborate an advisory guide on the mechanisms of social control and the application of resources destined to the financing of education in Cachoeira do Sul/RS. The methodological choices are based on a case study (YIN, 2010 and GIL, 2008), of qualitative approach (BOGDAN; BIKLEN, 2003). In addition, it was based on investigative analysis, which uses data triangulation (MINAYO, 2010), interweaving the legal documents, the bibliographies related to the theme and the data constructed throughout the research. The construction of the data came from the application of interviews with the presidents of CACS Fundeb and Alimentação Escolar of the municipality of Cachoeira do Sul/RS, supported by content analysis and document analysis of Bardin (2009). In the conclusion, it was evidenced the analysis of the categories of public policies and the financing of education: adjustments of the mechanisms, approval of accounts, budget 2022 and rational use of resources; categories of educational and social management: articulation between CACS and SMEd, planning and monitoring of actions and participation of social segments; and categories of training and information about the CACS: dissemination of the function of CACS, the role of councilors, guidelines for analysis and work reports. The proposed product is an advisory guide on the mechanisms of social control and the application of the resources destined to the financing of education in Cachoeira do Sul/RS, tied to an agenda of disclosure and training with the school communities, seeking to give access and expanding the information about the scenario of the financing of public education.